Gandhi, Deep Ecology, Peace Research and Buddhist Economics - THOMAS WEBER (Journal of Peace Research vol. 36, no. 3, 1999, pp. 349-361, 1999)
The central importance of Gandhi to nonviolent activism is widely acknowledged. There are also other significant peace-related bodies of knowledge that have gained such popularity in the West in the relatively recent past that they have changed the directions of thought and have been important in encouraging social movements - yet they have not been analysed in terms of antecedents, especially Gandhian ones. The new environmentalism in the form of deep ecology, the discipline of peace research and what has become known as `Buddhist economics' very closely mirror Gandhi's philosophy. This article analyses the Mahatma's contribution to the intellectual development of three leading figures in these fields: Arne Naess, Johan Galtung and E. F. Schumacher and argues that those who want to make an informed study of deep ecology, peace research or Buddhist economics, and particularly those who are interested in the philosophy of Naess, Galtung or Schumacher, should go back to Gandhi for a fuller picture.